Antigen-specific T lymphocyte clones. I. Characterization of a T lymphocyte clone expressing antigen-specific suppressive activity (The Rockefeller University Press, 1981)
We have generated continuously propagatable T lymphocyte clones to study antigen-specific T cell functions. All Ly-2+ clones mediate suppressive activity and secrete a characteristic pattern of polypeptides that differs from Ly-2- T cell clones. Cells of one clone, Cl.Ly23/4, specifically bind glycophorin from sheep erythrocytes (SRBC). After incubation with [35S]methionine, supernate material from this clone also contains biosynthetically labeled 70,000-mol wt proteins that specifically bind to SRBC and this binding is inhibited by glycophorin from sheep but not other erythrocytes. These antigen- binding 70,000-mol wt peptides specifically and completely suppress primary anti-SRBC responses generated by mixtures of primed Ly-1+2- cells and B cells. Suppression by these antigen-binding peptides reflects direct inhibition of T-helper activity.